Development of murine immune responses to H5 DNA vaccine with IRF3 as genetic adjuvant and HIV Tat-conjugated pamam dendrimer as the delivery system - Bahadoran, Azadeh (2016)
Influenza A virus is a major pathogen that represents an ongoing threat to several species as diverse as poultry, swine and mammals including humans health principally through their ability to cause respiratory morbidity and mortality. With the advances in modern vaccine technologies, several different vaccines are currently available against the Influenza A virus subtype H5N1. DNA vaccines have various attributes, which present them distinct advantages over other vaccine technologies in terms of safety, stability, ease of fabrication and immunogenicity. Although DNA vaccines offer a wide range of advantages, there is still a need to improve the delivery of DNA vaccines and to increase the immunogenicity of antigens expressed from the plasmids. Inefficient cellular delivery of DNA plasmids and insufficient stimulation of the innate immune system are considered as the main reasons for the failure of DNA vaccines to induce potent immune responses. In this study the immune responses of a new recombinant DNA vaccine encoding the H5 of avian influenza virus (AIV), green fluorescent protein (GFP) and Mus musculus interferon regulatory factor 3 (IRF3) genes (pBud-H5-GFP-IRF3) delivered via a platform for DNA delivery were evaluated. This platform is based on the use of generation 5 polyamidoamine (G5-PAMAM) dendrimers conjugated with HIV transactivator of transcription (TAT) as a cell-penetrating peptide. The expressions of H5 and IRF3 genes based on in vitro transfection study and the effect of TAT peptide on expressions of H5 gene in vitro transdermal transfection were evaluated as well as the immunogenicity of recombinant DNA plasmid delivered by different delivery systems based on in vivo animal study. The DNA plasmid constructs encoding H5, GFP and IRF3 genes were characterized using restriction enzyme analysis and sequencing prior to in vitro study. Effective conjugation of the TAT to the dendrimer was indicated by 1H-NMR and UV-visible spectroscopy. The interaction between PAMAM or TAT-PAMAM and the recombinant DNA plasmid was analyzed through the agarose gel retardation, DNase I protection assays and size, and zeta-potential measurements where all the analysis showed the designed platform able to form a compact and nanometre-sized polyplexes with DNA. In vitro study was performed by transient transfection of the constructed plasmids in Vero cell using PAMAM dendrimer followed by qualitative and quantitative analysis of the genes expression. The inserted genes in the DNA plasmid constructs were verified where significant expression of GFP, successfully transcriptional expression of the H5 and IRF3 genes and the detected expression of H5 and IRF3 proteins were observed by immunofluorescence assay, RT-PCR and Western blotting, respectively. In addition, the ability of PAMAM dendrimer to enhance the delivery of the DNA plasmid constructs was revealed. In order to examine and compare the effects of TAT conjugation structures on the efficacy of PAMAM dendrimers for gene delivery systems, transfection of recombinant plasmid was performed through artificial membrane (Pion PAMPA) followed by quantitative analysis of the genes expression. In vivo study was aimed to evaluate the immunogenicity of recombinant plasmid DNA, pBud-H5-GFP-IRF3 either using different delivery systems, including PAMAM dendrimer and TAT conjugated PAMAM dendrimer or the effect of the IRF3 as the genetic adjuvants in BALB/c mice. Mice were vaccinated intradermal and transdermal with naked DNA, PAMAM/H5-GFP, TAT-PAMAM/H5-GFP and TAT-PAMAM/H5- GFP-IRF3. The expression analysis of H5 gene from the blood by using qRT-PCR confirmed the ability of PAMAM dendrimer as carrier for gene delivery as well as the ability of TAT peptide to enhance the delivery efficiency of PAMAM dendrimer. Serum samples collected from the immunized group with TAT conjugated PAMAM dendrimer/H5-GFP pDNA elicited higher hemagglutination-inhibition (HI) titers compared to PAMAM dendrimer/H5-GFP pDNA exhibited the efficient gene delivery system when the PAMAM was modified with TAT peptide. The highest HI titer was achieved in mice vaccinated with TAT conjugated PAMAM dendrimer/ H5-GFP-IRF3 pDNA revealed the effect of IRF3 as genetic adjuvant on humoral immunity induction. TAT-PAMAM/H5-GFP-IRF3 also elicited CD3+/CD4+ and CD3+/CD8+ T cells in vaccinated mice. The modification of PAMAM dendrimer with TAT peptide resulted in <2-fold increases in the number of CD8+ T lymphocytes. The effects of TAT peptide for CD4+ T cells were not as significant as those for CD8+ T cells. Simultaneously study of the cytokines secreted including pro-inflammatory cytokines (IL-1β, TNF-α, IL-6), Th1 (IFN-γ, IL-2, IL-15, IL-12) and Th2 (IL-4, IL-10) was performed using multiplexed bead-based immunoassays. The highest level of the pro-inflammatory cytokines and Th1 cytokines including TNF-α, IL-6, IFN-γ and IL-12 were observed when PAMAM dendrimer was conjugated with TAT peptide. Additionally, co-administration of IRF3 as a genetic adjuvant showed the significant results in the expression levels of both proinflammatory and Th1 cytokines. Hence, administrations of the TAT conjugated PAMAM dendrimer recombinant plasmid H5-GFP-IRF3 (pBud-H5-GFP-IRF3) could induce strong antibody and both CD4+ and CD8+ T cell responses as well as enhanced cytokine productions against AIV in mice. This study provides valuable information for further study to determine the efficacy of the developed DNA vaccine to induce protection against challenge with virulent H5N1 virus.